2007
DOI: 10.1186/1471-2105-8-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

ProCMD: a database and 3D web resource for protein C mutants

Abstract: Background: Activated Protein C (ProC) is an anticoagulant plasma serine protease which also plays an important role in controlling inflammation and cell proliferation. Several mutations of the gene are associated with phenotypic functional deficiency of protein C, and with the risk of developing venous thrombosis. Structure prediction and computational analysis of the mutants have proven to be a valuable aid in understanding the molecular aspects of clinical thrombophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…Hereditary PC deficiency has an autosomal dominant mode of inheritance, but many reports also claimed autosomal recessive mode (Mohanty et al, 1995;Ehsan & Plumbley, 2002;Bereczky et al, 2010). Almost 250 different genetic defects have been reported so far to be associated with PC deficiency (Bertina, 1997;D'Ursi et al, 2007;Bereczky et al, 2010). The prevalence of PC deficiency has been reported to be one in 200 to 16,000 normal individuals in different studies (Miletich et al, 1987;Tait et al, 1995;Mohanty et al, 1995;Koster et al, 1995b;Ehsan & Plumbley, 2002).…”
Section: Protein C (Pc) Deficiencymentioning
confidence: 99%
“…Hereditary PC deficiency has an autosomal dominant mode of inheritance, but many reports also claimed autosomal recessive mode (Mohanty et al, 1995;Ehsan & Plumbley, 2002;Bereczky et al, 2010). Almost 250 different genetic defects have been reported so far to be associated with PC deficiency (Bertina, 1997;D'Ursi et al, 2007;Bereczky et al, 2010). The prevalence of PC deficiency has been reported to be one in 200 to 16,000 normal individuals in different studies (Miletich et al, 1987;Tait et al, 1995;Mohanty et al, 1995;Koster et al, 1995b;Ehsan & Plumbley, 2002).…”
Section: Protein C (Pc) Deficiencymentioning
confidence: 99%
“…(Figure 1). A recently developed mutation database, ProCMD, is an interactive tool that contains phenotypic descriptions with functional and structural data obtained by molecular modeling (47).…”
Section: Molecular Genetic Background Of Protein C and S Deficiency mentioning
confidence: 99%
“…To date, over 300 mutations have been reported. 11 Studies of PC mutations found significant differences regarding the ethnic background. For example, the p.R230C, p.Q132stop, p.R306stop, and c.3363insC mutations were commonly found in Caucasian populations, 12,13 whereas p.R147W, the c.C6152T in exon 7, causing a change in amino acid from arginine to tryptophan, was a common mutation among Taiwanese Chinese.…”
Section: Introductionmentioning
confidence: 99%